(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Polycystic Ovary Syndrome (PCOS) is a frequently occurring endocrine condition in women of reproductive age and a primary factor in subfertility linked to ovulation. Moreover, insufficient awareness regarding PCOS, its management, and lifestyle modifications affects the outcome. This qualitative research explores women’s understanding and perceptions of the syndrome, its treatment options, and the lifestyle modifications needed to combat it. A total of 120 individuals with PCOS were chosen through purposive sampling from Vriddhachalam. Telephonic interviews were carried out as well. The themes encompassed women’s understanding, causes, complications and risk factors, treatment of PCOS, and their perceived significance of health-promoting behaviors like physical activity, sleep habits, and perceived societal support. The significance of nutrition, physical activity, and a wellness-oriented lifestyle were other pertinent factors emphasized by the respondents. While the medications assisted participants in achieving consistent menstrual cycles, they also had side effects mentioned in the discussion. A small number of respondents indicated that they were unaware of PCOS when they were diagnosed in their youth. The research improves the comprehension of PCOS through a qualitative perspective that has cultural significance in addition to relevant clinical and lifestyle impacts.